Democratization through the looking glass - Burnell, Peter (Manchester University Press, 2003)
Democratization is a major political phenomenon of the current age. Democratization through the looking glass argues that our perspectives on democratization reflect the intellectual origins of the inquiry. How we see and understand it are influenced by what we 'bring to the table'. By considering democratization across a range of disciplines from anthropology and economics, to sociology, law and area studies, this volume offers a rich combination of analytical frameworks, distinctive insights and leading points of concern. On one level the book provides anyone interested in democratization with a wide-ranging distillation of the main themes, issues, and topics, concisely written by leading experts in their field. On a second level the book advances the case for a broadly-based comparative study which includes Europe and North America alongside developing regions, while maintaining the belief that a multi-disciplinary approach enhances our understanding of democratization far more than that of a narrow political science view. The book is aimed at students of politics willing to explore the boundaries of their subject and all social scientists who need an introduction to this important contemporary phenomenon.
English
Keywords: Political structures: democracy; sociology; democratization; politics; European Union